Rethinking Problematic Governance of Local Government in New Proliferated Regions and Their Impacts - Prasojo, Eko; Holidin, Defny (UI Scholars Hub, 2013)
Regional proliferation is a policy to improve governance of local governments upon decentralization taken into effect since 2001 in Indonesia in order to get public services in touch to the locals as well as further increases of prosperity level, but it is not necessarily proven as the matter of fact. This article gives a try to critically rethinking problematic situation of governing new municipalities upon proliferation, taking cases from Singkawang City and Bandung Barat Regency, to confirm previous theories. The study uses positivism approach by employing combining qualitative and quantitative method of inquiries through in-depth interviews to various actors, statistical analysis of conditions in comparison between those at the time of proliferation and recent progress, as well as content analysis of important documents. It suggests that regional proliferation in two municipalities implies double-edged impacts; they are opportunities to grasp local development on one side but counterproductive results of much dependency and stagnancy in local service delivery on the other side.